Linear-time snapshot protocols for unbalanced systems - Israeli, Amos; Shaham, Amnon; Shirazi, Asaf (1992)
Abstract: "The snapshot problem for shared memory systems is to enable a set of processors called scanners to obtain a consistent picture of the shared memory while other processors called updaters keep updating memory locations concurrently. One of the most intriguing open-problems in wait-free distributed computing is the existence of a linear-time solution to this problem. In this paper we show that if the number of either scanners of updaters is smaller than the square root of the total number of processors then such a linear solution exists."
Keywords: Computer network protocols